Influência da atividade e inatividade física na composição corporal e adiposidade central - Fernandes, Rômulo Araújo [UNESP]; Casonatto, Juliano; Christofaro, Diego Giuliano Destro; Buonani, Camila [UNESP]; De Oliveira, Arli Ramos; Freitas Jr., Ismael Forte [UNESP] (My University, 2010)
To analyze influences of the physical activity and sedentary behaviors on indicators of both central and total body fat in male adolescents. Cross-sectional study with 60 male students of age range from 11 to 14 years old. It were evaluated the body mass, height, triceps skinfold, waist circumference, body fat percentage (bioelectrical impedance) and the physical activity level through questionnaire. The physical inactivity prevalence was of 35%, and the excessive total and central body fat were observed in 38.3% and 48.3% of the sample, respectively. There was association of the sedentary behaviors with the excessive total and central body fat (OR = 5.2 e OR = 6.4, respectively), however there was not for physical activity. The adoption of sedentary behaviors is associated at the development of the total and central obesity among male adolescents.
Physical activity and inactivity effect on body composition and central adiposity
Keywords: Adolescents; Obesity; Physical activity; Physical inactivity